Impact of single nucleotide polymorphisms of immune checkpoint CTLA-4 (SNP rs231775 and rs5742909) in susceptibility to Hashimoto's thyroiditis patients - Asalh Mahmood; Risala Allami; Yasir Issa (Journal of Advanced Biotechnology and Experimental Therapeutics, 2024)
Background: Hashimoto thyroiditis is an autoimmune disorder causing thyroid cell destruction. This research aimed to evaluate CTLA-4 expression levels in patients with Hashimoto's thyroiditis, biochemical parameters. As well as understand the risk and protective effects of two CTLA-4 SNPs polymorphisms (rs231775 and rs5742909) in Iraqi patients. Methods: A case control study was conducted on 50 HT patients (5 men and 45 females) were assembled from Baghdad teaching hospital, Baghdad, Iraq. The relative Gene expression method was used to measure the gene expression of CTLA-4 using qRT-PCR. The single nucleotide polymorphisms of (318C/T (rs231775) and +49A/G (rs5742909) were sequenced for data analysis. Results: There was significant increase of serum CTLA-4 levels, similarity fold change of CTLA-4 was significant upregulated in HT patients compared to controls. The allele and genotypes frequencies according to HWB equilibrium showed significant differences in HT patients 318C/T (rs231775) AA genotypes, while no significant differences in the AG, GG genotypes, respectively compared to controls (p0.05). Both studied SNPs recoded higher upregulation of soluble and fold change of the immune check point (CTLA-4), respectively. Conclusion: The study reveals that CTLA-4 gene SNPs rs231775 and rs5742909 significantly influence soluble and the expression of CTLA-4 levels in HT patients, potentially causing Hashimoto disease and HT incidence and development. [ J Adv Biotechnol Exp Ther 2024; 7(1.000): 23-33]